Understanding International Students’ Perspective of Health Service Quality: A Cross-Sectional Study in a Hungarian University - Indrayathi PA; Ulandari LPS; Pradnyani PE; Dhamanti I; Kirshbaum MN; Szepesi CI; Horvath N; Kolozsvari LR (Dove Medical Press, 2024)
Putu Ayu Indrayathi,1- 3 Luh Putu Sinthya Ulandari,2 Putu Erma Pradnyani,4 Inge Dhamanti,5,6 Marilynne N Kirshbaum,7 Csongor Istvan Szepesi,1,3 Nora Horvath,1,3 Laszlo Robert Kolozsvari1,3 1Doctoral School of Health Sciences, University of Debrecen, Debrecen, Hungary; 2Department of Public Health and Preventive Medicine, Udayana University, Denpasar, Bali, Indonesia; 3Department of Family and Occupational Medicine, University of Debrecen, Debrecen, Hungary; 4Health Polytechnic Kartini Bali, Denpasar, Bali, Indonesia; 5Center of Excellence for Patient Safety Research and Quality, Universitas Airlangga, Surabaya, Indonesia; 6School of Psychology and Public Health, La Trobe University, Melbourne, Victoria, Australia; 7Charles Darwin University, Darwin, Northern Territory, AustraliaCorrespondence: Putu Ayu Indrayathi, Department of Family and Occupational Medicine, University of Debrecen, Móricz Zsigmond körút 22, Debrecen, 4032, Hungary, Email indrayathi.ayu@med.unideb.huPurpose: Understanding patient's preferences is important to delivering good quality services. Patients' feedback provides healthcare providers with valuable information about the services provided. The increasing number of international students enrolling in Hungarian Universities raises the need to ensure the quality of services meets international students' requirements, which includes healthcare. This study aimed to assess service quality in the University Health Center (UHC) from the international student's point of view to be used to improve the quality of services.Methods: This cross-sectional study was conducted at the university health center. We used a mixed methods approach to collect both quantitative and qualitative data. We used the importance-performance analysis (IPA) for quantitative analysis to understand expectations and perceptions in service research. The qualitative analysis was conducted from responses to reflection questions. The qualitative data were then analyzed using thematic analysis.Results: 437 international students participated in the study, but only 402 (91.99%) were analysed. The gaps between the importance and performance of service quality were negative in all dimensions (P-value < 0.001). This suggests that there is an unmet need for student expectations and university health center performance. From the Importance factor, the highest and lowest were related to safety (4.54 ± 0.56) and efficiency (4.31 ± 0.66) dimensions. The Performance factor's highest and lowest mean scores were also related to safety (4.22 ± 0.72) and efficiency (3.91 ± 0.87), respectively. From qualitative analysis, there are two major themes several secondary themes from the thematic analysis of free-text responses were identified.Conclusion: The importance and performance analysis could provide useful information to university policymakers about university health center service quality. There is a need for improvement and obviating the importance-performance gaps, especially in the efficiency dimension. Decision-makers can use the IPA analysis results to allocate limited resources more effectively, giving special attention to possible organizational weaknesses for further direction.Keywords: healthcare, service quality, international students